Validation of the Critical Care Pain Observation Tool in Critically Ill Patients With Delirium: A Prospective Cohort Study. Issue 5 (May 2016) - Kanji, Salmaan; MacPhee, Heather; Singh, Avinder; Johanson, Christel; Fairbairn, Jennifer; Lloyd, Tammy; MacLean, Robert; Rosenberg, Erin
Abstract : Objectives: The 2013 clinical practice guidelines for the management of pain, agitation, and delirium in adult patients in the ICU suggest that pain be routinely assessed using a validated pain assessment tool. Currently available tools have only been evaluated in nondelirious critically ill patients, yet delirium can affect as many as 80% of ICU patients. The validated pain assessment tool adopted by our institution is the Critical Care Pain Observation Tool, and the objective of this study was to investigate the validity of this tool in patients with evidence of delirium. Design: Prospective cohort study. Setting: Two ICUs within a Canadian tertiary healthcare center. Patients: Forty consecutive adult patients deemed delirious on the day of enrollment using the Confusion Assessment Method for ICU. Measurements and Main Results: Serial Critical Care Pain Observation Tool assessments were conducted simultaneously by study personnel and objective nurses at baseline and after nonpainful and painful stimuli. Subjective opinions about pain and objective physical variables (including mean arterial pressure, heart rate, respiratory rate, and oxygen saturation) were collected at the same time points. Discriminant validity was described using paired t tests, whereas internal consistency was described using the Cronbach α statistic. Responsiveness of the Critical Care Pain Observation Tool was measured by effect size, and reliability was described as the agreement between raters. Comparisons between the Critical Care Pain Observation Tool and the subjective assessments and objective measurements were based on positive and negative percent agreement. Critical Care Pain Observation Tool demonstrated excellent discriminant validity as evidenced by a highly statistically and clinically significant change in mean Critical Care Pain Observation Tool scores between baseline and painful procedures (mean difference, 3.13 ± 1.56; p < 0.001; Cohen D, 2.0). Interrater agreement was also excellent ( κ > 0.6), and scores between raters were highly correlated ( r = 0.957). The Critical Care Pain Observation Tool possessed a high level of internal consistency (overall Cronbach α, 0.778). Percent agreement was found to be greater between the Critical Care Pain Observation Tool and the nurse's subjective opinion of the presence or absence of pain when compared with that between the Critical Care Pain Observation Tool and physiologic variables (80.5% vs 67.5%, respectively). Conclusions: The Critical Care Pain Observation Tool is a valid pain assessment tool in noncomatose, delirious adult ICU patients who are unable to reliably self-report the presence or absence of pain.